PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA PASAR PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fitri Veta Viyan; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research is to examine empirically the influence of intellectualcapital to market performance. In this study intellectual capital consists of threeaspects, human capital, structural capital and capital employee is measured by theVAICTM. While the market performance is determined by the price to book value ratio.Ownership structure as a control variable. Because in Indonesia the ownershipstructure can be concentrated so that it can influence the market appraisal. Thepopulation in this study is a company listed on the Indonesia Stock Exchange. Thesample in this study is a company that is in Indonesia Stock Exchange in 2014-2016.With purposive sampling method. Methods of statistical analysis used multipleregression. The results show that intellectual capital of human capital, structuralcapital, capital employee and ownership structure simultaneously had a significanteffect on market performace. While partially, the intellectual capital of human capitalsignificantly affect the market performance. Intellectual capital of structural capitalnot significantly affect the market performance. Intellectual capital of capitalemployee not significantly affect the market performance. Ownership structuresignificantly affect the market performance.Keywords: intellectual capital, market performance, ownership structure